Experimental investigation of streamer radius and length in SF6. (18th May 2015) - Bujotzek, M; Seeger, M; Schmidt, F; Koch, M; Franck, C
Abstract: SF6 has for decades been widely used in high voltage insulation and switching applications, e.g. in gas insulated switchgear. Despite its widespread use some important parameters, like the properties of streamers, are still not sufficiently understood. Since breakdown in SF6 always occurs via the streamer-leader transition the streamer properties are decisive for leader inception and, therefore, breakdown of the insulation. Important parameters are, for example, the streamer radius and the streamer propagation length of arrested streamers. Such properties enter in breakdown prediction models. In the present study the streamer radius and the propagation length were investigated experimentally at 50 and 100 kPa for both polarities using strongly and weakly non-uniform background fields. No experimental information was available so far for negative polarity. The resulting streamer radius scaling agrees with previous experimental results for positive polarity and with expectations from breakdown models for negative polarity. These results were similar for strongly non-uniform and weakly non-uniform background fields. A difference between the two setups was observed for the streamer lengths. It was found that for strongly non-uniform fields the streamer length scales as expected with the critical electric field but with a different field for weakly non-uniform background fields. This was similar for both polarities.